Relative Impact of Different Strategies for Allocating Federal Funds for Syphilis Prevention - Chesson, Harrell W. (Sex Transm Dis, 2018)
BACKGROUND: Improvements in resource allocation can increase the benefits of federally funded sexually transmitted disease (STD) prevention activities. The purpose of this study was to illustrate how different strategies for allocating federal funds to subnational districts for syphilis prevention might affect the incidence of syphilis at the national level. METHODS: We modeled syphilis rates by district and year using an equation based on a previous analysis of state-level syphilis elimination funding and syphilis case rates from 1998 to 2005 in the United States. We used the model to illustrate the potential impact of 3 different strategies for allocating supplemental federal funds to subnational districts to support syphilis prevention activities a hypothetical country with 18 subnational districts. The 3 strategies were based on each district’s (1) population size, (2) syphilis incidence rate, or (3) number of syphilis cases. The hypothetical country was similar to the United States in overall population and syphilis burden. RESULTS: Without the supplemental federal funds, there would be an estimated 48,600 incident infections annually in the hypothetical country. With the supplemental federal funds, the annual number of infections would be reduced to 27,800 with a population-based allocation of funding to each district, 26,700 with a rate-based allocation, and 24,400 with a case-based allocation of funding. CONCLUSIONS: Allocating federal STD prevention funds to districts based on burden of disease can be an efficient strategy, although this efficiency may be reduced or eliminated when high-burden districts have less ability to provide adequate STD prevention services than lower-burden districts.